Around seven decades river course shifting and bank erosion susceptibility of river Mujnai. Issue 2 (9th November 2022) - Sarkar, Sudipa; Bera, Biswajit
Abstract: River bank erosion is a destructive fluvio‐hydrological hazard particularly inhabited flood plain of the dynamic Himalayan foreland basin. Every year during monsoonal months, morphology of the landscape is continuously modifying through the dynamic river system. The principal objectives of this study are (i) to identify the river bank erosion susceptibility through BESI (River Bank Susceptibility Index) model which has been modified from Rosgen's (2001) Bank Erosion Hazard Index (BEHI) model and historical reconstruction (from 1955 to 2021) of the river course of Mujnai and (ii) to examine the principal factors of river bank erosion particularly for the river Mujnai within Himalayan Foreland Basin. Sedimentary bank facies analysis has also been done to ascertain the causes of river bank instability. Hence, rate of bank migration, changes of channel width, channel sinuosity index (SI), channel length, erosion and accretion of the river bank, and so forth have been measured through geospatial techniques. Result showed that the younger Quaternary sediments are prone to erosion and BESI result illustrated that around 28% areas are under high erosion zones like Deoagaon, Dhulagaon, Hedayet Nagar, and Dalimpur villages in Alipurduar district. Average maximum width of the channel was recorded in 1980 (147.92 m). Additionally, the lateral migration in case of left bank was around 141.08 m (in the 1980) and 192.62 m in right bank (in 1980) while the shifting rate was 14.10 m/y and 17.51 m/y respectively. Quaternary bank materials, bioturbation and indistinct laminations of river bank are principal regulating factors behind bank erosion in this area. Monsoonal high‐velocity flow, bank full discharge and severe flood incidents accelerate the bank erosion vulnerability, particularly in this dynamic flood plain. Soft engineering techniques such as bioengineering, geo‐textile fabric, tree, grass and brush revetment should be implemented at high bank erosion vulnerable sites of river Mujnai.